2021
DOI: 10.1038/s41746-021-00536-y
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting adverse surgical events using self-supervised transfer learning for physiological signals

Abstract: Hundreds of millions of surgical procedures take place annually across the world, which generate a prevalent type of electronic health record (EHR) data comprising time series physiological signals. Here, we present a transferable embedding method (i.e., a method to transform time series signals into input features for predictive machine learning models) named PHASE (PHysiologicAl Signal Embeddings) that enables us to more accurately forecast adverse surgical outcomes based on physiological signals. We evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 60 publications
0
47
0
Order By: Relevance
“…This represents an example where the complementary relationship between humans and machines can outperform either one alone. More recently Chen et al ( 37 ) tested a transferable embedding method (i.e., a method to transform time series signals into input features for predictive ML models) named PHASE (PHysiologicAl Signal Embeddings) with a large amount of dataset from ORs and ICU. Results indicated that PHASE outperforms other state-of-the-art approaches in predicting six distinct outcomes: hypoxemia, hypocapnia, hypotension, hypertension, phenylephrine, and epinephrine ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…This represents an example where the complementary relationship between humans and machines can outperform either one alone. More recently Chen et al ( 37 ) tested a transferable embedding method (i.e., a method to transform time series signals into input features for predictive ML models) named PHASE (PHysiologicAl Signal Embeddings) with a large amount of dataset from ORs and ICU. Results indicated that PHASE outperforms other state-of-the-art approaches in predicting six distinct outcomes: hypoxemia, hypocapnia, hypotension, hypertension, phenylephrine, and epinephrine ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we argue that transfer learning might be a promising and feasible strategy to maintain the effectiveness of the trans-center deployment of machine learning models. Furthermore, transfer learning has been applied to similar domains or similar tasks in several medical fields, reducing the size requirements of the target dataset, and improving the training speed and the prediction performance [ 35 38 ]. In our context, transfer learning can be used to predict different types of diseases, such as disseminated intravascular coagulation (DIC) or acute kidney injury (AKI).…”
Section: Discussionmentioning
confidence: 99%
“…Having the possibility of a direct recording, with the minimum human interference, could allow instead to increase the quality of the dataset and therefore obtain more precise results. [19][20][21] Furthermore, having a system equipped with the ability to independently record the patient's movements, could be able, in addition to reducing the error rate, to lighten the workload of the operators themselves and indirectly reduce the changeover times between the different patients. [17,21−25] Nevertheless, building a tracking system inside a hospital is not a simple task.…”
Section: Discussionmentioning
confidence: 99%